Comparative assessment of antibacterial drugs used at the hospital level before and during COVID-19, according to the WHO AWaRe classification - Balapasheva, Aigerim A.; Smagulova, Gaziza A.; Mussina, Aigul Z.; Dilmagambetov, Daniyar S.; Yermekbayeva, Kalzhan Zh.; Kelimberdiev, Mirsaid S.; Kulnazarova, Mariya S.; Balymbetova, Lazzat S.; Ziganshina, Liliya E. (Frontiers in Pharmacology, 2025)
Antimicrobial resistance is a major global challenge, and the World Health Organization (WHO) promotes the Access, Watch, and Reserve (AWaRe) classification to support rational antibiotic use. In Kazakhstan, irrational prescribing remains common, and the COVID-19 pandemic intensified the misuse of broad-spectrum antibiotics. A retrospective study at a hospital in Aktobe (2019–2021) analyzed antibiotic use from pharmacy and medical records using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) methodology, with categorization by the WHO AWaRe classification. The analysis revealed a persistent predominance of “Watch” antibiotics, particularly cephalosporins, fluoroquinolones, and carbapenems, with their use intensifying during the COVID-19 pandemic. The share of “Access” antibiotics remained well below the WHO-recommended target of 60%, fluctuating between 24% and 27% across the study period. Reserve antibiotics were not prescribed. The findings reveal gaps in antibiotic stewardship in Kazakhstan: overreliance on “Watch” antibiotics and underuse of “Access” drugs, contrary to WHO guidance. Implementing the AWaRe framework with national targets and monitoring is essential, and the study adds regional evidence to the global AMR discourse, underscoring the need for stronger policies, especially during pandemics.